Relationship between consumption of soft and alcoholic drinks and oral health problems - Çetinkaya, Hatice; Romaniuk, Piotr (Central European journal of public health, 2020)
OBJECTIVES: Oral health can affect quality of life in all course of life, which is a key factor of general health. Dental caries, periodontitis and oral cancer are of the highest burden of oral diseases. Rising prevalence of soft drinks and alcoholic beverages consumption due to easy access and socio-demographic altering has increased the concerns on oral health. In this review our purpose was to show effects of the most consumed beverages on oral health in people older than 15 years. METHODS: The review was based on papers published in last 10 years, searched with combined key words related to types of drinks and specific oral health problems. We included 4 older studies due to lack of newer studies on subjected topics. RESULTS: Sugar-free soft drinks are found less cariogenic and erosive than regular versions in limited number of studies. Alcohol consumption is shown as one of the risk factors of prevalence and severity of periodontitis and is proven to have synergistic effects along with tobacco on oral cancer risk. Consumption of soft drinks and alcoholic beverages was related with tooth loss whether dental caries or periodontal diseases. CONCLUSION: There is good evidence for association between soft drinks and oral health problems, but still no clear answer exists about strength of association between sugar-free soft drinks and dental caries. Also the knowledge about influence of alcohol is inadequate. Since consuming style affects erosive potential of drinks manufacturers should be required to add some recommendations on labels about drinking style.
Keywords: Dietary Sucrose; orální zdraví; Carbonated Beverages; Humans; kvalita života; carbonated drinks consumption; Beverages; Dental Caries; konzumní sacharóza; Quality of Life; nápoje; sycené nápoje; alkoholické nápoje; oral health; Oral Health; dental health; sugar sweetened beverages; lidé; zubní kaz; Alcoholic Beverages; alcohol consumption